Digital-Era Approaches to Teaching Reading in Arabic as a Second Language: A Case Study of Al Jazeera Arabic Learning | Manāhij al-‘Ashr al-Raqmī fī Ta’līm Mahārah al-Qirāah lil Lughah al-‘Arabiyyah Lughah Tsāniyah: Dirāsah al-Hālah ‘alā Al Jazeera li Ta’allum al-‘Arabiyyah - Fadli, Hafidz; Soekarba, Siti Rohmah; Ramadhanti, Nur Malihah Fawwaz; Letmiros, Letmiros; Al-Haqbani, Amar (UIN Sunan Gunung Djati Bandung, 2024)
This study examines effective strategies for teaching Arabic reading skills using qualitative research methods, a case study, and a thematic approach. It aims to formulate practical techniques and procedures to enhance Arabic reading proficiency. Reading skills, a crucial component of language acquisition, encompass various forms, such as loud reading, silent reading, intensive reading, extensive reading, critical reading, basic reading, analytical reading, interactive reading, and inferential reading. This study uses a qualitative approach using descriptive methods and employs two frameworks: the thematic approach and the case study approach. The study highlights how teaching Arabic as a second language has evolved to align with digital advancements, with software and platforms like Al Jazeera Arabic Learning playing a pivotal role. These tools provide structured modules to facilitate language learning, offering students and educators innovative approaches to reading comprehension. The findings suggest that integrating digital tools into language curricula can enhance the effectiveness of teaching strategies and foster greater engagement among learners. Future research should explore the long-term impact of digital tools on Arabic language acquisition, compare traditional and digital methods, and develop specific frameworks for integrating technology into Arabic education. Additionally, investigating students' and teachers' perceptions of these tools could inform the development of more user-centered educational technologies.